The Roles of Magnetorheological Fluid in Modern Precision Machining Field: A Review - Lu, He; Hua, Dezheng; Wang, Baiyi; Yang, Chengli; Hnydiuk-Stefan, Anna; Królczyk, Grzegorz; Liu, Xinhua; Li, Zhixiong (Frontiers in Materials, 2021)
Owing to some specific advantages, magnetorheological fluid (MRF) has drawn significant attention in a broad range of modern precision machining field. With the diversification and improvement of demands, many novel structure configurations and processing methods have been applied to mechanical machining equipment. Although different applications with MRF have been proposed in existing literature, the classification, latest approaches and further trend are not involved clearly for machining field. Thus, the current applications used MRF are summarized from 2016 to 2020, which include machining auxiliary equipment and surface polishing equipment in this work. Especially, some detailed structures of equipment are investigated and relative limitations are analyzed based on the characteristics of MRF. Finally, in view of the current equipment, advantages and defects are briefly reported; the developing trends of modern precision machining with MRF are discussed. Therefore, in the state-of-the-art review, increasingly important role of MRF are emphasized for the machining field, which are conducive to innovative developments and market selection.